2014
DOI: 10.4102/sajpsychiatry.v20i1.441
|View full text |Cite
|
Sign up to set email alerts
|

Children and adolescents treated for post-traumatic stress disorder at the Free State Psychiatric Complex

Abstract: <p><strong>Background.</strong> Children and adolescents can develop post-traumatic stress disorder (PTSD) after exposure to a range of traumatic events, including domestic, political or community violence, violent crime, physical and sexual abuse, hijacking, witnessing a violent crime and motor vehicle accidents. This is particularly critical given the substantial challenge that PTSD poses to the healthy physical, cognitive and emotional development of children and adolescents.</p><… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Previous research found that 90% of South African youth reported being a witness of physical violence in their neighborhood and 48% reported seeing at least one murder in their lifetime (Shields, Nadasen, & Pierce, 2008; Ward et al, 2001). PTSD prevalence among South African adolescent samples ranges between 3.5% and 5.8% in general community samples, but prevalence rates are relatively unknown among clinic samples (Calitz, de Jongh, Horn, Nel, & Joubert, 2014; Ward et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research found that 90% of South African youth reported being a witness of physical violence in their neighborhood and 48% reported seeing at least one murder in their lifetime (Shields, Nadasen, & Pierce, 2008; Ward et al, 2001). PTSD prevalence among South African adolescent samples ranges between 3.5% and 5.8% in general community samples, but prevalence rates are relatively unknown among clinic samples (Calitz, de Jongh, Horn, Nel, & Joubert, 2014; Ward et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It includes all painful thoughts, images, perceptions and repeated nightmares related to the traumatic event in addition to psychological stress and physiological pain. This dimension includes (16) items (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: First Dimension: Recallmentioning
confidence: 99%
“…In some cases, symptoms last for short time and disappear quickly but in other cases it may last for months or even years (41: 581). (11) who indicated that post-traumatic disorder includes several other psychological disorders that may appear individually or as a set. These include anxiety, depression, poor expression of emotions and thoughts and emotional disorder.…”
Section: Introduction and Research Problemmentioning
confidence: 99%
“…Children experience traumatic events in three ways; directly experiencing a traumatic event; witnessing such events; traumatic event happening for a loved person. Reactions such as fear, terror, helplessness, shame and guilt experienced during or after traumatic events are reactions frequently given responses to traumatic events [2]- [4]. These reactions may be more severe and long-lasting based on severity and fearsomeness of traumas experienced by children.…”
Section: Children's Mental Traumamentioning
confidence: 99%